The relationship between body mass index and clinical properties/survival in patients with breast cancer - Erdoğdu, Batuhan; Utkan, Güngör (The European Research Journal, 2023)
Objectives: The aim of this study was to investigate relationship between body mass index (BMI) and recurrence/survival and to determine whether body mass index is a risk factor. Methods: A retrospective study of 125 patients with breast cancer was performed. Age, sex, menopausal situation, body mass index, tumor size, axillary lymph node involvement and number, tumor degree, hormone receptor situation, cerbB-2 overexpression, tumor grade, chemotherapy dose and treatments, radiotherapy, metastasis, comorbidity, total survival and time of death were evaluated. Patients were compared as BMI < 30 kg/m2 and BMI ≥ 30 kg/m2. Kaplan-Meier method and Log Rank test was utilized for the overall survival of patients. Results: In these 72 patients, 57.6% of patient’s body mass index BMI < 30 kg/m2 (non-obese) while 53 of the group (42.4%) BMI ≥ 30 kg/m2 (obese) were found in the group. The median follow-up was 158.32 months (95% CI: 130.45 to 186.19). The mean follow-up was 146 ± 46 months (95% Cl: 55.36-236.63) and 144 ± 28 months (95% CI: 88.19-199.81) for non-obese patients and obese patients respectively. Kaplan Meier plots were drawn for determination of the effect of body mass index in total survival. No significant difference was found statistically between two groups. Conclusions: No significant difference was found statistically between BMI and recurrence/death. The future studies with long term follow up are needed to investigate the effect of body mass index on recurrence and survival in patients with breast cancer.